The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1007/s00426-017-0935-x
|View full text |Cite
|
Sign up to set email alerts
|

Humans show a higher preference for stimuli that are predictive relative to those that are predictable

Abstract: Recent studies suggest that humans prefer information that is linked to the process of prediction. Yet it remains to be specified whether preference judgments are biased to information that can be predicted, or information that enables to predict. We here use a serial reaction time task to disentangle these two options. In a first learning phase, participants were exposed to a continuous stream of arbitrary shapes while performing a go/no-go task. Embedded in this stream were hidden pairs of go-stimuli (e.g., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…An important role of unexpected events, or prediction errors, has more recently been suggested in aesthetic judgment (Chetverikov & Kristjánsson, 2016;Trapp, Shenhav, Bitzer, & Bar, 2015;Van de Cruys et al, 2014;Van de Cruys & Wagemans, 2011). One recent study observed a higher preference for predictive stimuli relative to non-predictive (i.e., randomly predictive) ones (Braem & Trapp, 2017). This seems consistent with the decreasing trend at the right side of the inverted-U, although we must be cautious: First, this work found an effect specifically for predictive, not for predictable, stimuli.…”
Section: Discussionsupporting
confidence: 80%
“…An important role of unexpected events, or prediction errors, has more recently been suggested in aesthetic judgment (Chetverikov & Kristjánsson, 2016;Trapp, Shenhav, Bitzer, & Bar, 2015;Van de Cruys et al, 2014;Van de Cruys & Wagemans, 2011). One recent study observed a higher preference for predictive stimuli relative to non-predictive (i.e., randomly predictive) ones (Braem & Trapp, 2017). This seems consistent with the decreasing trend at the right side of the inverted-U, although we must be cautious: First, this work found an effect specifically for predictive, not for predictable, stimuli.…”
Section: Discussionsupporting
confidence: 80%
“…Reducing uncertainty and increasing predictability has been discussed as a fundamental human need (Heider, 1958;Hogg, 2000;Kagan, 1972), with the pleasure of predictability deriving from the perceived ability to anticipate and control our environment. Whereas predictability facilitates attentional orienting, processing, and performance (e.g., Alink et al, 2010;Coull & Nobre, 1998;Posner et al, 1980) and is processed as rewarding by the brain (e.g., Braem & Trapp, 2019;Trapp et al, 2015), unpredictability is experienced as aversive (e.g., Heine et al, 2006;Proulx et al, 2012;Schubert et al, 2017;Topolinski & Strack, 2015) and increases stress and physiological arousal (e.g., de Berker et al, 2016;Herry et al, 2007;Jackson et al, 2015;Mendes et al, 2007;Peters et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…When eventually asked which layout they prefer, participants significantly chose the predictive over the random layout. Braem and Trapp ( 2019 ) showed that when exposed to a series of subsequently presented stimuli with hidden pairs, i.e., one stimulus predicted the occurrence of another, participants preferred the stimulus that had helped them to make predictions over random and over the predicted stimulus. This could indicate that facilitated predictive processing is tagged as inherently positive.…”
Section: Predictions and Affectmentioning
confidence: 99%